Efficient Secured Cloud Storage System using Dynamic Multiple Clouds Cryptographic Algorithm - Kavuri, Venkata Ramaiah; T. P., Anithaashri (International Conference on I-SMAC (IoT in Social, Mobile, Analytics and Cloud) (Online), 2023)
Recently, Cloud Computing has become a crucial technology since it provides various services like distributed applications, Ecommerce, Social Media Streaming services, Email activities, Storing files and Banking services. In general, IT Field requires in-depth cloud coding knowledge and deploy apps to become cloud expert. Cloud storage is a way of storage mechanism of automated digital data storage to store that information remotely and save different type of data securely so that it can be accessed at anytime from anywhere. Cloud Computing is a comfortable secured way of travel for the huge amount of data packages produced by the IoT through the cyberspace. Here, our aim to prevent Data leakage, intellectual property theft, malware attacks, control Hackers and also control insecure access points. The proposed system focuses on Different types of cloud technologies like private clouds, multi clouds, hybrid clouds and public clouds to provide services to their customers and minimize security issues, cost effective and data leakage problems. IoT provides huge number of smart and intelligent devices. These devices cater to both local and remote needs. Nowadays encryption algorithms are needed to provide security to the data on the internet. Dynamic Multiple Clouds Cryptographic Algorithm (DMCCA) is an encryption algorithm. This wave provides high security and lower computations. This algorithm is a combination of RSA and Blow Fish algorithms [6] [7]. Comparing RSA and Blow Fish algorithms efficiency and speed of DMCCA algorithm is high. It also verifies cloud administration to improve their distributed file accessing. Finally, for future work, our aim to supply dynamic secure cloud database and improves different clouds storage capacity in all remote areas.